2017
DOI: 10.3390/economies5030034
|View full text |Cite
|
Sign up to set email alerts
|

A Firm-Level Investigation of Innovation in the Caribbean: A Comparison of Manufacturing and Service Firms

Abstract: A lack of growth remains a major concern for Caribbean countries. Private sector development has been identified as vital in addressing this problem. Innovation, a necessary condition for competitiveness, is a key channel through which the private sector can help to stimulate growth. An analysis of innovation at the firm level for Caribbean manufacturing and services sectors shows that patent rights, the level of domestic sales, collaboration for innovation purposes, innovation intensity (that is, the efficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 40 publications
1
1
0
Order By: Relevance
“…For instance, several studies conducted in specific developing economy such as Abdu and Jibir (2017) in Nigeria, El Elj (2012) in Tunisia and Goedhuys (2007) in Tanzania find similar evidence that firm size, ownership status, export status and being a part of a large firm affects a firm's probability to innovate. According to these findings, previous studies conducted in developing regions such as Alleyne et al (2017) in Caribbean Fernandez (2017) in Latin American countries show similar results.…”
supporting
confidence: 83%
“…For instance, several studies conducted in specific developing economy such as Abdu and Jibir (2017) in Nigeria, El Elj (2012) in Tunisia and Goedhuys (2007) in Tanzania find similar evidence that firm size, ownership status, export status and being a part of a large firm affects a firm's probability to innovate. According to these findings, previous studies conducted in developing regions such as Alleyne et al (2017) in Caribbean Fernandez (2017) in Latin American countries show similar results.…”
supporting
confidence: 83%
“…Moreover, it is pointed out that customers contribute to developing productivity (Spohrer and Maglio, 2008) and also the role of advanced technologyinnovativeness (Matuzeviciute, Butkus, and Karaliute, 2017;Jakimowicz and Rzeczkowski, 2019a;Jakimowicz and Rzeczkowski, 2019b). Studies on the impact of innovation on average productivity growth, both in the service sector and the manufacturing sector, were conducted by Alleyne, Lorde, and Weekes (2017). The authors observed that higher innovation intensity is associated with more incredible productivity growth (in both sectors).…”
Section: Introductionmentioning
confidence: 99%